An improved node algorithm based on the evaluation of weighted network node importance. Issue 1 (March 2018) - DengWei, Lin
There are shortcomings in the node contraction method used in the evaluation of the importance of weighted network nodes. To avoid those defects, an improved importance evaluation method is proposed. The differences of edge weight have impacts on importance of nodes and edges; therefore, two improvements are made in defining the network cohesion and the importance of edges of network G* using weighted shortest distances. In this paper, this improved method is analyzed and validated through a comparative analysis. The influence of the coefficients on the importance and relative importance of the nodes is analyzed by adjusting the proportional coefficient and the weight coefficient. The results show that the improved method can provide more comprehensive and accurate assessment of the importance of weighted network nodes without increasing the computational complexity.